Assessing Genetic Variants in Matched Biocompartments From Patients With Serous Ovarian Cancer. (24th June 2021) - Sanders, Brooke E.; Ku, Lisa; Walker, Paul; Bitler, Benjamin G.
The clinical use of molecular tumor profiling (MTP) is expanding and there is an increasing use of MTP data to manage patient care. At the University of Colorado, 18 patients were diagnosed with primary serous ovarian cancer between 9/2015 and 6/2019 and consented for banking and analysis of tumor, ascites and plasma. All 18 patients had tumor and plasma samples that were sent for MTP, and 13 of 18 patients additionally had ascites collected and sent for MTP. 50-gene panel testing and BRCA testing were performed on primary tumor. BRCA genetic variants were more likely to be identified in plasma as compared to ascites or tumor, though not statistically significant ( P = 0.17). Co-occurring genetic variants between plasma and ascites were less common in comparison to co-occurring variants between tumor and plasma or tumor and ascites, though not statistically significant ( P = 0.68). Variants in KDR (VEGFR2) and TP53 were most likely to be conserved across all 3 biocompartments. Mutant allele frequencies (MAF) of individual genetic variants varied across biocompartments, though tended to be highest in the tumor, followed by ascites.